2022
DOI: 10.1101/2022.02.15.480622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-nucleus transcriptomic analysis reveals divergence of glial cells in peripheral somatosensory system between human and mouse

Abstract: Glial cells play a crucial role in regulating physiological and pathological functions, such as sensation, infections, acute injuries, and chronic neurodegenerative disorders. Glial cells include astrocytes, microglia, and oligodendrocytes in the central nervous system (CNS) and satellite glial cells (SGCs) in the peripheral nervous system (PNS). Despite the understanding of glial subtypes and functional heterogeneity in animal models achieved by single-cell or single-nucleus RNA sequencing, no research has in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…To evaluate the potential relevance of our results from mouse models to human conditions, we performed snRNA-seq analysis of human lumbar spinal cords and compared their neuron and astrocyte subtypes with that of mouse spinal cords. We found that, the human neurons 31 and astrocytes 32 and the mouse counterparts showed similar clusters based on the transcriptomic characteristics, suggesting the similar heterogeneity in neurons and astrocytes of human and mouse spinal cords. In addition, we compared the expression profiles of Wnt5a in neurons and ROR2 in astrocytes, and observed that Wnt5a was expressed in homologous neuronal clusters (Suppl.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…To evaluate the potential relevance of our results from mouse models to human conditions, we performed snRNA-seq analysis of human lumbar spinal cords and compared their neuron and astrocyte subtypes with that of mouse spinal cords. We found that, the human neurons 31 and astrocytes 32 and the mouse counterparts showed similar clusters based on the transcriptomic characteristics, suggesting the similar heterogeneity in neurons and astrocytes of human and mouse spinal cords. In addition, we compared the expression profiles of Wnt5a in neurons and ROR2 in astrocytes, and observed that Wnt5a was expressed in homologous neuronal clusters (Suppl.…”
Section: Discussionmentioning
confidence: 62%
“…The snRNA-seq results for Wnt5a in neurons and ROR2 in astrocytes came from the deposited large datasets that published in bioRxiv 31, 32 . snRNA-seq was performed as described 31 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it will be interesting to determine the role of UNC80 and UNC79 in pain and sensation, which might also be novel targets for controlling pain. More importantly, although NALCN is also widely expressed in the human DRG and spinal cord Zhang et al, 2022), evidence that NALCN regulates pain in humans has not yet been found. Future studies are needed to explore whether NALCN is a key target for controlling human pain, which will spur drug development and facilitate successful clinical translation from rodent findings.…”
Section: Strengths and Weaknesses Of The Current Evidence Regarding T...mentioning
confidence: 99%
“…Notably, whether reduced NALCN activity in the DRG and/or spinal cord leads to abnormal biological functions, such as motor behaviors, needs to be validated in future studies. A recent study revealed that NALCN is also expressed in the glial cells of the DRG and spinal cord in both humans and rodents (Zhang et al, 2022). The role of NALCN in glial cells should also be determined, as the activities of glial cells are involved in pain sensation.…”
Section: Perspectivesmentioning
confidence: 99%